New functions of an old kinase MPK4 in guard cells. (4th May 2018) - Lin, C.; Chen, S.
ABSTRACT: Mitogen-activated protein kinase (MPK) cascades play important roles in plant development, immune signaling and stress responses. MPK4 was initially identified as a negative regulator in systemic acquired resistance (SAR) because the levels of salicylic acid (SA) and reactive oxygen species (ROS) were higher in the Arabidopsis mpk4 mutant. MPK4 is highly expressed in guard cells, specialized epidermal cells forming stomatal pores on leaf surface that function at the frontline of bacterial pathogen invasion. In addition to biotic stresses, stomatal guard cells also mediate cellular responses to abiotic stimuli such as drought and CO2 changes. MPK4 appears to play different roles in different plant systems. In this review, we briefly discuss the protein kinase MPK4 functions and focus on its signaling roles in different plant systems, especially in stomatal guard cells.